Analysis of Repeated CT Scan Need in Blunt Head Trauma - Eroglu, Serkan Emre; Onur, Ozge; Ozkaya, Sefer; Denızbasi, Arzu; Demır, Hasan; Ozpolat, Cıgdem (Emergency Medicine International, 2013)
Background. Computed tomography (CT) is a vital tool in the workup of patients with closed head trauma. The aim of this study was to investigate the necessity of serial CT scans in patients with blunt head trauma. Methods. This is a retrospective study analyzing trauma patients between January and June 2012. Data were analysed by using frequencies, Kolmogorov-Smirnov (K-S), and Chi-square tests. Results. Of the total 351 control Head CTs, it was seen there were no different in 346 (98.6%). In CTs of another 3 patients (0.9%), there were increasing or new, in the other 2 (0.6%) there was a decrease in the pathology present. Of 24 (6.8%) patients who had a hemorrhage in the first CT, there was an increase in the hemorrhage in one of them, a decrease of the pathology in 2 of them. Of 27 (7.7%) patients who had fracture in first CT, 2 had a new intracranial hemorrhage. The relation of the results between the first and second CTs were statistically significant (P<0.001, χ2 test). Conclusion. Repeated CT scans after 6 hours in EDs observation rooms are not necessary if first CT is normal in most situations. Special attention may be needed in patients with an underlying chronic disease.